2020
DOI: 10.1002/oa.2918
|View full text |Cite
|
Sign up to set email alerts
|

The application of quantitative petrography and macroscopic colour change in a comparative analysis of Roman and Anglo‐Saxon cremation practices

Abstract: The microscopic examination of burned bone has allowed cremation research to infer a wealth of information concerning burning practices and pyre technology from archaeological contexts. Recently, a new approach for quantifying the microscopic heat-induced alterations in burned bone to categorise burning intensity using petrography has been developed within histomorphological studies. The following study is the first application of quantitative petrography to examine cremated remains from two archaeological con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…the cremator or cremation operator) could have been a ritual specialist, a skilled worker (e.g. a smith or a potter) (Goldhahn & Oestigaard 2008;McKinley 2015;2016;Carroll & Squires 2020), or perhaps a family member (Oestigaard 2000). The transformation of the dead body from flesh to burnt bones and ash requires technical knowledges regarding the management of funeral pyre, which is linked to the skills and specialisation of the cremator (Cenzon-Salvayre 2014).…”
Section: Introductionmentioning
confidence: 99%
“…the cremator or cremation operator) could have been a ritual specialist, a skilled worker (e.g. a smith or a potter) (Goldhahn & Oestigaard 2008;McKinley 2015;2016;Carroll & Squires 2020), or perhaps a family member (Oestigaard 2000). The transformation of the dead body from flesh to burnt bones and ash requires technical knowledges regarding the management of funeral pyre, which is linked to the skills and specialisation of the cremator (Cenzon-Salvayre 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to this innovative study, it was suggested that temperatures of ≥ 900 °C obliterated all dental microstructures 40 , 41 . Consequently, no IGD would be visible in cremated human teeth, since the average temperature of outdoor pyres is postulated to be between 800 °C and 900 °C 39 , whereby experimental outdoor pyre cremations showed that temperatures of 1000 °C can also be reached for a short period of time 44 and some may even reach higher temperatures 45 . However, this study clearly shows that IGD remains visible in dentine burned at 900 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Since the colour of most of retrieved dentine in archaeological cremation deposits is grey to white (see Fig. 5 ), the first set of teeth was burned at 600 °C for the duration of 2 h since this is the expected minimum temperature of an archaeological pyre, which could result in the observed colours 16 , 45 . The second set of teeth was burned at 800 °C (for 2 h), which is expected to be the average temperature of the pyres, based on the macroscopic assessment of the cremation material (i.e.…”
Section: Methodsmentioning
confidence: 99%